Breast cancer—The catalyst of contemporary trials design. Issue 1 (13th December 2021) - Al‐Hilli, Zahraa; Weiss, Anna; Armani, Ava; Boughey, Judy C; Blair, Sarah L.
Abstract: Surgical trials in breast cancer have catalyzed contemporary trial design for solid organ cancers and are a prime example of surgeons taking the lead in clinical trial design. Surgeons have lead trials that have improved patient outcomes and quality of life without sacrificing oncologic safety. We have evolved from radical mastectomy to breast conservation and sentinel node biopsy. Contemporary trial design in breast cancer now focus on personalizing care based on tumor genomics